Vocational Rehabilitation in Small and Medium-sized Enterprises An Integrated Management Perspective on Potentials and Business Impact - Miethlich, Boris (Logos Verlag Berlin, 2022)
After an accident or severe illness, it may be difficult or even impossible to return to work due to a long absence from work or lasting impairments. In this case, vocational rehabilitation takes place in addition to health-related rehabilitation. There is some evidence in the literature that vocational rehabilitation contributes to increasing the profitability of companies. However, this phenomenon has not yet been comprehensively empirically researched. Therefore, this dissertation analyses and operationalise, from a holistic management perspective, the direct and indirect impacts of vocational rehabilitation on business. Besides, an explanatory model is provided for the optimal implementation of vocational rehabilitation and to realise the emerging potential. A commitment to vocational rehabilitation does not directly but indirectly influence business performance. The direct impact of vocational rehabilitation is mainly at the operational level, which interacts with the normative level. The business performance benefits are realised primarily at the strategic level. This phenomenon is also reflected in the insight that vocational rehabilitation has a leverage effect on the existing resources and competencies. Furthermore, there is a positive correlation between the level of vocational rehabilitation integration, the maturity of the company culture and the increasing contribution to business performance.